2011
DOI: 10.1007/s12035-011-8213-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurexins and Neuroligins: Recent Insights from Invertebrates

Abstract: During brain development, each neuron must find and synapse with the correct pre-and postsynaptic partners. The complexity of these connections and the relatively large distances some neurons must send their axons to find the correct partners makes studying brain development one of the most challenging, and yet fascinating disciplines in biology. Furthermore, once the initial connections have been made, the neurons constantly remodel their dendritic and axonal arbours in response to changing demands. Neurexin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 109 publications
1
62
0
Order By: Relevance
“…290286 had a 630-kb duplication at chr22:33,440,702-34,073,409 and exhibited a phenotype of global developmental delay and delayed gross motor development. In addition, complex rearrangement or duplication may cause gene mutations, which lead to cognitive disorders, such as ASD if such genes are important in the development and modulation of synaptic connectivity (12). While sequencing the 15 exons of this gene did not identify any significant mutations, it is suggested that the duplication associated with ASD is more frequent in males.…”
Section: Discussionmentioning
confidence: 98%
“…290286 had a 630-kb duplication at chr22:33,440,702-34,073,409 and exhibited a phenotype of global developmental delay and delayed gross motor development. In addition, complex rearrangement or duplication may cause gene mutations, which lead to cognitive disorders, such as ASD if such genes are important in the development and modulation of synaptic connectivity (12). While sequencing the 15 exons of this gene did not identify any significant mutations, it is suggested that the duplication associated with ASD is more frequent in males.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, mutations in many different synaptic signaling pathways and effector genes have been identified by genetic screens, revealing that synapse morphogenesis requires a complex conversation between motor neurons and muscle that requires a combination of secreted factors (particularly important BMP and Wnt-family members [18, 19]), synaptic adhesion molecule (e.g. FasiclinII, Neurexin and Neuroligan, Teneurins [2022]), and extracellular matrix [23]. Although activity-dependent control of NMJ morphogenesis was discovered decades ago [5], the advent of a simple acute stimulation paradigm [11]** created an opportunity to study mechanisms required to initiate bouton formation.…”
Section: Activity Induced Budding Of Presynaptic Terminalsmentioning
confidence: 99%
“…In addition, α-Neurexins contain fi ve sites for alternative splicing in the region encoding the ectodomain, two of which are also present in β-Neurexins. These splice sites enable the generation of multiple splice variants of both α-and β-Neurexins [reviewed in Craig and Kang ( 2007 ) and Knight et al ( 2011 )]. …”
Section: Interactionsmentioning
confidence: 99%